Encyclopedia of Life Sciences 2017
DOI: 10.1002/9780470015902.a0027076
|View full text |Cite
|
Sign up to set email alerts
|

Brain Growth in H omo erectus

Abstract: Humans' massive brains stand out as one of our species' defining features. Growth and development are the means by which our large brains are achieved, and these mechanisms also distinguish us from other animals. The evolution of brain growth is difficult to reconstruct as fossil samples are generally small, and brain growth occurs within a minuscule proportion of an individual's life. Although there are several nonadult hominin cranial fossils, the earliest specimen to shed light on this issue is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Several studies over the past century have shown the specific gravity of neural tissue in humans and other primates to be roughly 1.036 g/cm 3 (Blinkov & Glezer, ; Davis & Wright, ; Frontera, ; Gompertz, ; Klekamp, Riedel, Harper, & Kretschmann, ; Stephan, ). As such, it is common to compare BM and ECV by either dividing the former or multiplying the latter by this specific gravity (e.g., Barrickman, , ; Barrickman & Lin, ; Cofran, ; DeSilva & Lesnik, ; DeCasien, Williams, & Higham, ; Kuzawa et al, ; Leigh, , ; Stephan, Frahm, & Baron, ). Providing empirical support for this conversion, Isler et al () examined the relationship between these two measures of brain size in a large adult sample representing the diversity of the order Primates.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies over the past century have shown the specific gravity of neural tissue in humans and other primates to be roughly 1.036 g/cm 3 (Blinkov & Glezer, ; Davis & Wright, ; Frontera, ; Gompertz, ; Klekamp, Riedel, Harper, & Kretschmann, ; Stephan, ). As such, it is common to compare BM and ECV by either dividing the former or multiplying the latter by this specific gravity (e.g., Barrickman, , ; Barrickman & Lin, ; Cofran, ; DeSilva & Lesnik, ; DeCasien, Williams, & Higham, ; Kuzawa et al, ; Leigh, , ; Stephan, Frahm, & Baron, ). Providing empirical support for this conversion, Isler et al () examined the relationship between these two measures of brain size in a large adult sample representing the diversity of the order Primates.…”
Section: Methodsmentioning
confidence: 99%